Effect of Electrolyte Imbalance on Mortality and Late Acute Kidney Injury in Hospitalized COVID-19 Patients (Iranian Journal of Kidney Diseases, 2022)
Introduction. As a multisystem illness, Coronavirus disease 2019 (COVID-19) can damage different organs. This study investigated the effect of electrolyte imbalance (EI), with or without concomitant renal dysfunction, on the prognosis of COVID-19 in hospitalized patients. Methods. We evaluated 499 hospitalized patients with confirmed COVID-19, without a history of chronic kidney disease. The patients’ demographic data, laboratory values, and outcomes were retrospectively collected from the hospital information system. Serumelectrolytes including sodium, potassium, magnesium, calcium, and phosphorus abnormalities were analyzed on admission and during the hospitalization period. The outcomes of this study were the occurrence of acute kidney injury (AKI) after the first week of hospitalization and in-hospital mortality rate. Multivariate analyses were carried out to obtain the independent risk of each EI on mortality, by adjusting for age, gender, and AKI occurrence. Results. Among the 499 COVID-19 patients (60.9% male), AKI occurred in 168 (33.7%) and mortality in 92 (18.4%) cases. Hypocalcemia (38%) and hyponatremia (22.6%) were the most prevalent EIs, and all EIs were more common in the AKI group than in the non-AKI group. Hyponatremia (Adjusted Odds ratio [AOR] = 2.34, 95% CI: 1.30 to 4.18), hypernatremia (AOR = 8.52, 95% CI: 1.95 to 37.32), and hyperkalemia (AOR = 4.63, 95% CI: 1.65 to 13) on admission were associated with poor prognosis. Moreover, hyponatremia (AOR = 3.02, 95% CI: 1.28 to 7.15) and hyperphosphatemia (AOR = 5.12, 95% CI: 1.24 to 21.09) on admission were associated with late AKI occurrence. Conclusion. This study highlights the role of hyponatremia, hypernatremia, hyperkalemia, and hyperphosphatemia in poor prognosis of COVID-19. According to the independent effect of EI on late AKI and mortality, we recommend physicians to raise awareness to closely monitor and correct EI during hospitalization.  DOI: 10.52547/ijkd.6904